1999
DOI: 10.1038/13273
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Measuring protein conformational stability is one key to solving the protein folding problem. The conformational stability is the free energy change of the unfolding reaction, F ↔ U, under ambient conditions, ∆G U = G U -G F . Traditional methods of measuring ∆G U are solvent (urea or guanidinium chloride (GdmCl)) or thermal denaturation 1 . Solvent denaturation curves are generally analyzed using the linear extrapolation method (LEM):where m is a measure of the dependence of ∆G on denaturant, and ∆G U (H 2 O)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…After earlier suggestions supported mainly by temperature dependence studies (53, 54), the calibration of unprotected HX rates (3, 11, 45) (k ch in Equation 1) made it possible to compute unfolding free energy based on HX rates of the slowest hydrogens in any given protein (Equation 3). The agreement of these values with global stability measured by standard methods as well as their large dependence on denaturant and temperature revealed that proteins experience transient global unfolding/refolding reactions even under stable native conditions (4, 20, 28). One consequence is that proteins may spontaneously unfold and refold many times, in whole or in part, during their lifetime, as considered below.…”
Section: Protein Opening Reactionssupporting
confidence: 55%
“…After earlier suggestions supported mainly by temperature dependence studies (53, 54), the calibration of unprotected HX rates (3, 11, 45) (k ch in Equation 1) made it possible to compute unfolding free energy based on HX rates of the slowest hydrogens in any given protein (Equation 3). The agreement of these values with global stability measured by standard methods as well as their large dependence on denaturant and temperature revealed that proteins experience transient global unfolding/refolding reactions even under stable native conditions (4, 20, 28). One consequence is that proteins may spontaneously unfold and refold many times, in whole or in part, during their lifetime, as considered below.…”
Section: Protein Opening Reactionssupporting
confidence: 55%
“…Second, GDP-tubulin exhibits a step in the denaturation curve with a midpoint of approximately 0.125 M urea. Third, as H/D exchange correlates with protein conformational stability (39), GTP-tubulin is more stable than either GDP-tubulin or GMPCPP-tubulin up to approximately 0.5 M urea. Fourth, GMPCPP-tubulin is markedly less stable than GTP-tubulin over most of the concentration range but most notably in the absence of urea.…”
Section: Resultsmentioning
confidence: 99%
“…This can account for the mix of hydrogen bonds being stabilized, destabilized, or unaffected by ligand binding that is stabilizing to the ground state 26 . Estimations of global folding stability using the amide groups most protected from HX 25 are not, however, affected by localized accelerations of HX. The folding stability estimated for the entire enzyme suggests that the X1P-bound state is globally stabilized by ~0.6 kcal/mol over the E P state.…”
Section: Resultsmentioning
confidence: 98%
“…Conditions of pH 7.4 and 35 °C ensured that the HX behavior of the X1P complex occurred in the bimolecular EX2 regime, where the residues with the largest ΔG HX can be used to estimate folding stability by the method of ref. 25. Both subsecond HX and slow hydrogen-deuterium exchange (HDX) of E P +X1P were measured, revealing rate constants and ΔG HX for 201 amide groups.…”
Section: Resultsmentioning
confidence: 99%